Descriptive sensory analysis and consumers' preference for dietary fibre- and polyphenol-enriched tomato purees obtained using winery by-products. Issue 1 (June 2015) - Torri, Luisa; Piochi, Maria; Lavelli, Vera; Monteleone, Erminio
Abstract: The sensory profile and consumers' acceptability of fibre- and polyphenol-enriched functional tomato purees were studied. Products were developed by incorporating different granulometric fractions of grape skins (S ≤ 125 μm; 125 μm < M ≤ 250 μm; 250 μm < L ≤ 500 μm) in two tomato puree types (V and R). A significant increase in textural (crispiness, granularity) and odour (spicy, hay) attributes and a decrease in perceived homogeneity and astringency were observed as the particle size increased. Based on consumer clustering, two drivers for product optimization were identified. Cluster 1 significantly preferred the smoothest particle size, and the drivers of formulations that were preferred seemed to be the flavour of processed tomato and homogeneity. By contrast, Cluster 2 preferred the coarsest particle size where the sensations of fresh tomato were enhanced as well as the sensations of crispiness, granularity and vegetable notes. The finest particle size was the most suitable when combined with the V type, while the coarsest particle size performed best when combined with the R tomato type. Highlights: Formulations of tomato purees and grape skins (GS) granulometric fractions were studied. Increase in GS particle size enhanced perception of textural and odour attributes. Increase in GS particle size decreased perceived homogeneity and astringency. Consumers showed different preferences for finest and coarsest GS particle sizes. Fine and coarse GS particle sizes were suitable for Smooth and Rough purees, respectively.